GREEN-FUNCTION FOR A SPIN-1/2 PARTICLE IN AN EXTERNAL PLANE-WAVE ELECTROMAGNETIC-FIELD - Vaidya, A. N.; Hott, M. (Iop Publishing Ltd, 1991)
The Green function for a spin-1/2 charged particle in the presence of an external plane wave electromagnetic field is calculated by algebraic techniques in terms of the free-particle Green function.